Neurofibromatosis and Schwannomatosis - Plotkin, Scott R.; Wick, Antje (Seminars in neurology, 2018)
Neurofibromatosis 1, neurofibromatosis 2, and schwannomatosis are a group of related classically inherited but often times sporadic tumor suppressor syndromes. Neuro-oncologists should recognize these syndromes, initiate necessary tests in patients with a clinical suspicion, and support genetic counseling of patients and families. In this review, clinical presentation, diagnostic criteria, day-to-day management including supportive care as well as updates on genetics, and experimental treatment strategies are discussed.
Gesehen am 23.04.2020